Remote sensing of bush encroachment on commercial cattle farms in semi-arid rangelands in Namibia - Matthias Schröter; Oliver Jakoby; Roland Olbrich; Marcus Eichhorn; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
Bush encroachment is one of the most extensive changes in land cover in Namibia and an urgent problem for cattle farming, rapidly reducing the productivity of the rangeland. Despite the severity of these consequences, a complete and accurate assessment of bush encroached areas is still missing at large. This study aims at assessing bush encroachment on commercial cattle farms in central Namibia by employing remote sensing methods to distinguish between areas covered by bush and open rangeland. Herein we use different classification techniques and vegetation indices to characterize the nature of vegetation cover. Our analysis shows that results are sensitive to specific classifications of indices. As an accuracy assessment could not be run on these results we could not analyze which classification approximates real bush encroachment best. Hence, this study highlights the need for further analysis. Ground truth data, in the form of field mappings, high resolution aerial photographs or local expert knowledge are needed to gain further insights and produce reliable results.
Keywords: Q57; Q15; Q24; 330; Remote sensing; semi-arid rangelands; cattle farming; bush encroachment